DEVELOPMENT OF A MATHEMATICAL MODEL OF THE SPREAD OF DUST AND SALT PARTICLES FROM ECOLOGICALLY DAMAGED SOIL SOURCES - Yarashov , Inomjon Kakhramonugli; Subhonov , Muhammad Rashidugli (Sanoatda raqamli texnologiyalar, 2024)
The growing focus on ecological issues has led to extensive research on the dispersion of harmful particles. Numerical modeling is used to simulate these particles and track their concentration changes. Key indicators, such as soil physical and chemical properties, are considered in the modeling process. This simplifies the process, allowing for more accurate mathematical models that predict harmful particle behavior. This approach enhances understanding of ecological processes and supports strategies for mitigating harmful particle effects and improving environmental management practices.